Administration Management at Madrasah Aliyah - Salabi, Ahmad (Indonesian Journal of Educational Studies, 2014)
This study aimed to describe the administratiion management at Madrasah Aliyah. This research was conducted with a qualitative descriptive approach. Data sourced from MA NIPA and MA NIPI RAKHA, Amuntai, South Kalimantan. Data collection techniques used in this study were (1) interview, (2) observation, and (2) documentation. Data were analyzed using a flow model of Miles and Huberman. The results showed that (1) the administrative management of madrasah aliyah are good category, (2) the principal role as managers and administrators with good category.